Resilience thinking: a bibliometric analysis of socio-ecological research - Xu, L.; Marinova, Dora (Springer, 2013)
Resilience thinking is a rising topic in environmental sciences and sustainability discourse. In this paper, a bibliometric method is used to analyse the trends in resilience research in the contexts of ecological, economic, social, and integrated socio-ecological systems. Based on 919 cited publications in English which appeared between 1973 and 2011, the analysis covers the following issues: general statistical description, influential journal outlets and top cited articles, geographic distribution of resilience publications and covered case studies, national importance of resilience researchers and leading research organisations by country. The findings show that resilience thinking continues to dominate environmental sciences and has experienced a dramatic increase since its introduction in 1973. More recently, new interest has emerged for broadening the scope and applying the concept to socio-economic systems and sustainability science. The paper also shows that resilience research overall is dominated by USA, Australia, UK and Sweden, and makes the case for the need to expand this work further in the urgent need for practically oriented solutions that would help arrest further ecological deterioration.